VIRTUAL KITS IN TECHNICAL EDUCATION - SERAFIN, Cestmir (Trends in education, 2010)
This paper focuses on a new phenomenon - virtual instruments in the form of kits. You are a computer similar to a real bricks, created a special program in either computer or even animations as flesh on the internet. Replace the kit if the computer program, we get into the virtual world, which is very close to today's children and computer games. Proximity of these phenomena, it is appropriate to use just the attraction of learning and interest of students, stimulate their creativity and technical development thinking
Keywords: kits; information technology; program; education.